Problem-Based Learning Model to Improve High School Students' Knowledge of Athletics Sports Material Learning Achievement - Pratomo, Eko Setya (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
The objective of this study was to determine the improvement of student learning achievement in athletics material through the problem-based learning model. This type of research is classroom action research with two cycles. At MA Al-Hikmah Purwoasri, the research sample consisted of 24 students. We conducted this research through a cycle of planning, implementation, observation, reflection, and data collection. The instruments used in this study were test and observation techniques. The data analysis used a quantitative description. The results of the study showed that there was a significant increase in student athletics learning achievement after the problem-based learning model was implemented. This is clear from the results of cycle I, where 47% of the students did not meet the minimum completion criteria of 75, and the class average was only 78.01. On the other hand, cycle II results showed that 91.18% of the 24 students who took the test met the minimum completion criteria of 75. Therefore, the application of the problem-based learning model can enhance student learning achievement in athletics material, particularly in the high jump.